Internal nasal dilator in patients with obstructive sleep apnea syndrome and treated with continuous positive airway pressure - Gelardi, Matteo; Intiglietta, Pierluigi; Porro, Giuseppe; Quaranta, Vitaliano Nicola; Resta, Onofrio; Quaranta, Nicola; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
The nasal valve area has the minimal cross-sectional area of the upper airways. Obstructive sleep apnea syndrome (OSAS) is a common disorder. It has been reported that nasal obstruction may be associated with OSAS. The aim of this study was to investigate whether the use an internal nasal dilator may be able to affect respiratory pattern in a group of patients with OSAS and treated with continuous positive airway pressure (CPAP). The use of internal nasal dilator significantly reduced the pressure of CPAP (from 11.4±1.5 to 10.8±1.5; p=0.012) able to resolve apnea episodes. In conclusion, this study showed that Nas-air® is a new internal nasal dilator potentially capable to significantly improve adherence and compliance to CPAP.